2015
DOI: 10.1016/j.bjid.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Detection of E. coli O157:H7 and Shigella dysenteriae toxins in clinical samples by PCR-ELISA

Abstract: Shiga toxin producing bacteria are potential causes of serious human disease such as hemorrhagic colitis, severe inflammations of ileocolonic regions of gastrointestinal tract, thrombocytopenia, septicemia, malignant disorders in urinary ducts, hemolytic uremic syndrome (HUS). Shiga toxin 1 (stx1), shiga toxin 2 (stx2), or a combination of both are responsible for most clinical symptoms of these diseases. A lot of methods have been developed so far to detect shiga toxins such as cell culture, ELISA, and RFPLA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 28 publications
(35 reference statements)
1
31
0
Order By: Relevance
“…It has been reported that S. dysenteriae was detected in feces by immune-magnetic isolation and PCR in about 7 h 5 . As stated by a group, the presence of inhibitors is one of the potential problems of PCR and may cause false results also 1 . Sensitivity of PCR for detection of pathogens in food products depends strongly on the procedure of DNA extraction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that S. dysenteriae was detected in feces by immune-magnetic isolation and PCR in about 7 h 5 . As stated by a group, the presence of inhibitors is one of the potential problems of PCR and may cause false results also 1 . Sensitivity of PCR for detection of pathogens in food products depends strongly on the procedure of DNA extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Mousavi uated a PCR-enzyme-linked immunosorbent assay for sensitive and rapid detection of V. cholera O 1 from Iran. In our previous study, PCR-ELISA was used to detect genes encoding shiga toxins1 and 2 from Escherichia coli O157: H7 and other Shiga toxin-producing E. coli (STEC) (33). In our procedure, we used DNA genomic ETEC; we also decreased the number of PCR cycles to five for reducing the reaction time.…”
Section: Discussionmentioning
confidence: 99%
“…The “gold standard” for detecting E. coli O157:H7 in food samples is a traditional separation-identification method which is time-consuming (at least five days) and laborious (involves pre-enrichment, selective enrichment, culture isolation, and identification). Other methods, including the polymerase chain reaction (PCR) [2,3] and enzyme-linked immunosorbent assay (ELISA) [4,5], also may require laborious procedures and expensive instruments.…”
Section: Introductionmentioning
confidence: 99%